METODE TAFSIR AMINAH WADUD - Rheina Fattah N.H; Romi Ananda (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
Amina Wadud in the introduction to one of her books, "The Qur'an According to Women: Re- reading the Holy Scriptures with the Spirit of Justice", states that it is not the text of the Koran that limits women, but the interpretation of religious texts which limits them which are considered more important than the Koran itself. Amina also revealed that the importance of analyzing the concept of the Koran about women must be measured from the perspective of the Koran itself, both as a strength in history, politics, language, culture, scholarship, and spirituality, as well as a holy book. The study of Amina Wadud Muhsin's method in understanding the verses of the Koran seeks to reinterpret various verses of the Koran that have tended to be interpreted patriarchically by classical commentators, so the method used in interpreting the Koran uses holistic approach.